2015
DOI: 10.1016/j.socscimed.2014.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Can education rescue genetic liability for cognitive decline?

Abstract: Although there is a vast literature linking education and later health outcomes, the mechanisms underlying these associations are relatively unknown. In the spirit of some medical literature that leverages developmental abnormalities to understand mechanisms of normative functioning, we explore the ability of higher educational attainments to “rescue” biological/genetic liabilities in brain function through inheritance of a variant of the APOE gene shown to lead to cognitive decline, dementia, and Alzheimer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 42 publications
2
37
0
2
Order By: Relevance
“…On the other hand, they highlight the vulnerability of adults with high genetic risks for T2D who attain low levels of education. Cook and Fletcher (2015) similarly examine whether education suppresses genetic health risks. They explore the ability of higher education to "rescue" liabilities in brain function due to the inheritance of the E4 variant of the APOE gene, which is correlated with cognitive decline, dementia and Alzheimer's disease.…”
Section: More Years Of Schooling Appears To Suppress Genetic Risks Fomentioning
confidence: 99%
“…On the other hand, they highlight the vulnerability of adults with high genetic risks for T2D who attain low levels of education. Cook and Fletcher (2015) similarly examine whether education suppresses genetic health risks. They explore the ability of higher education to "rescue" liabilities in brain function due to the inheritance of the E4 variant of the APOE gene, which is correlated with cognitive decline, dementia and Alzheimer's disease.…”
Section: More Years Of Schooling Appears To Suppress Genetic Risks Fomentioning
confidence: 99%
“…High levels of socioeconomic status in adulthood may mediate the relationship between early-life conditions and late-life cognitive function (Lyu and Burr, 2016), but do not completely eliminate the effect of early-life adversities (Zhang et al, 2016). Higher levels of schooling and better schooling performance are also linked to both better CH and slower rates of cognitive aging (Cook and Fletcher, 2015; Herd, 2010), and this education-cognition nexus is possibly even more important in LMIC contexts than high-income countries (Huang and Zhou, 2013). Cognitive reserves, measuring the ability of individuals to cope better with adverse influences on CH, have been shown to vary significantly among individuals, particularly at older ages and often as a function of individuals’ life course (Stern, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, a growing literature in different disciplines has documented geneenvironment interactions that refers differential responses to the effects of a genotype based on environmental conditions or vice versa (e.g., Guo, Roettger, and Cai 2008;Cook and Fletcher 2015a;Caspi and Moffitt 2006). These studies have suggested that although genetic variants are determined at conception and rarely change over the life course, their effects may not be deterministic because their phenotypic manifestations are often subject to environmental influences.…”
Section: Gene-environment Interactions In Obesitymentioning
confidence: 99%
“…Although genetic variants are determined at conception and do not change except through epigenetic modifications and DNA mutations, a gene-environment interaction framework suggests that their effects may not be deterministic because their phenotypic manifestations are often subject to environmental influences throughout the life course (e.g., Guo, Roettger, and Cai 2008;Cook and Fletcher 2015a). A few studies have suggested that the effects of so-called "obesity genes" on the development of obesity may be moderated by environmental factors.…”
Section: Introductionmentioning
confidence: 99%